(untitled) (International Educators Conference, 2025)
This study examines the role of fluency and accuracy in English language teaching (ELT) and their influence on effective language acquisition. Fluency focuses on learners’ ability to communicate ideas smoothly and naturally, while accuracy emphasizes the correctness of grammar, vocabulary, and pronunciation. The paper explores pedagogical approaches that balance these elements, considering the context of learner needs, goals, and proficiency levels. It discusses how prioritizing either fluency or accuracy impacts language competence and offers strategies for integrating both in classroom practices. Additionally, the research highlights the significance of creating communicative opportunities for students to practice fluency while refining accuracy through corrective feedback and targeted activities.